2020
DOI: 10.1186/s41938-020-00280-7
|View full text |Cite
|
Sign up to set email alerts
|

Life table and demographic parameters of the coccinellid predatory species, Hippodamia convergens Guérin-Méneville (Coleoptera: Coccinellidae) when fed on two aphid species

Abstract: The study aimed to determine the effect of two aphid species; Lipaphis erysimi (Kaltenbach) and Aphis gossypii Glover (Hemiptera: Aphididae) on life table and demographic parameters of Hippodamia convergens Gu`erin-M´eneville (Coleoptera: Coccinellidae). The developmental period of all life stages of H. convergens was shorter when fed on L. erysimi. Net reproductive rate (Ro) was higher (159.85 offspring/individual) on L. erysimi, while it was 87.85 offspring/individual on A. gossypii. Mean generation time (T)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 30 publications
4
5
2
1
Order By: Relevance
“…The instantaneous rate of population increase (r m ) refers to the maximum population growth rate under optimal space, food, and intraspecific influence, and is considered the most useful life table parameter for comparing the growth rates of different populations (Price, 1984). The r m values found for C. sanguinea, H. convergens, and H. axyridis in this study are higher than those reported in previous studies (Lanzoni et al, 2004;Milléo et al, 2014;Zazycki et al, 2015;Arshad et al, 2020). The high values of r m shown by these coccinellids here demonstrated that S. graminum is a suitable essential prey for them (Hodek and Evans, 2012).…”
Section: Discussioncontrasting
confidence: 65%
See 4 more Smart Citations
“…The instantaneous rate of population increase (r m ) refers to the maximum population growth rate under optimal space, food, and intraspecific influence, and is considered the most useful life table parameter for comparing the growth rates of different populations (Price, 1984). The r m values found for C. sanguinea, H. convergens, and H. axyridis in this study are higher than those reported in previous studies (Lanzoni et al, 2004;Milléo et al, 2014;Zazycki et al, 2015;Arshad et al, 2020). The high values of r m shown by these coccinellids here demonstrated that S. graminum is a suitable essential prey for them (Hodek and Evans, 2012).…”
Section: Discussioncontrasting
confidence: 65%
“…Female coccinellids tend to disperse as a strategy to disperse their eggs widely in the area where they live (Evans, 2003). Although the dynamics of searching behavior of coccinellids is not sufficiently understood (Pervez and Yadav, 2018), the present findings indicated that the almost constant reproductive activity that continues through the entire In comparison to the fecundity values found for the coccinellids in the current study, Arshad et al (2020) reported lower values for H. convergens fed on the aphids Aphis gossypii Glover (251.0 eggs per female) and Lipaphis erysimi (Kalt.) (319.7 eggs per female) (Hemiptera: Aphididae).…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations